The economic and social model of the nordic EU members: Growth, innovation and budgetary discipline despite high government spending rates - Ognian N. Hishow (Stiftung Wissenschaft und Politik (SWP), 2005)
At the EU summit in Hampton Court on 27 and 28 October in discussions of a suitable European economic and social model that could assure sustainable prosperity and help master the challenges of the future, repeated reference was made to the performance of the Nordic member states. Despite - or because of - the high public sector share of GDP, all three countries have achieved budget surpluses and have low levels of income inequality. Yet there is no uniform Nordic model of employment and taxation. Striking differences exist between the individual countries. Finland suffers from persistent unemployment; Denmark has the most business-friendly tax policies in the EU; and Sweden has drastically cut back its welfare state. In the meantime the reduction of the government share of GDP has become a common feature of all three countries. Although a transfer of the Nordic system to the large EU economies is not possible for structural and historical reasons, individual economy-policy elements can indeed be adopted. (SWP-Comments / SWP)
Keywords: 320